The environmental costs of Peru's domestic air transport: an appraisal - Defilippi, Enzo (2018)
The purpose of this paper is to estimate CO2 emissions from Peru’s domestic air transport. This is basic and relevant information for public policy making that has not been calculated before. The estimation has been performed using destination, frequency and aircraft related data of all domestic flights that departed or landed at Jorge Chavez International Airport, a hub that accounts for over 93% of the country’s domestic air passenger traffic. CO2 emissions were estimated using a methodology proposed by the International Civil Aviation Organization that differentiates fuel usage during each phase of a flight. Results show that, in 2014, Peruvian domestic air transport was responsible for emitting approximately 606,975 tons of CO2. This is equivalent to US$4.35 million or US$59.4 per one-way flight. These results could be used as an input to assess how to internalize the externalities caused by air transport to society and thus, to improve the efficiency and effectiveness of the country's environmental policy.